Enduring attenuation of norepinephrine synaptic availability and augmentation of the pharmacological and behavioral effects of desipramine by repeated immobilization stress. (1st May 2017) - Gonzáles, Marco A.; Miranda, Ana Pamela; Orrego, Horacio; Silva, Rodolfo; Forray, María Inés
Abstract: Here we provide evidence that repeated immobilization stress (RIS) in rats induces a persistent increase in noradrenergic activity in the anterior aspects of the anterolateral bed nucleus of the stria terminalis (alBNST). This increase in noradrenergic activity results from both enhanced synthesis and reuptake of norepinephrine (NE). It leads to a decrease in the synaptic availability of NE, which elicits an augmented noradrenergic response to the inhibitors of NE reuptake (NRIs), such as desipramine (DMI), an antidepressant. The enduring depression-like behavior and the augmentation of the climbing behavior seen in repeatedly stressed rats following subchronic administration of DMI in the forced swimming test (FST) might be explained by a dysregulation of noradrenergic transmission observed in alBNST. Taken together, we propose that dysregulation of noradrenergic transmission such as the one described in the present work may represent a mechanism underlying major depressive disorders (MDD) with melancholic features in humans. Highlights: RIS increases the tonic noradrenergic activity in the alBNST. RIS decreases NE availability in the alBNST by enhancing its reuptake. RIS induces depression-like behavior in the FST. RIS induces an augmented response to desipramine in the FST. The effects of RIS persist for 22 days following the exposure to stress.